2022
DOI: 10.1371/journal.pgen.1010097
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale fungal strain sequencing unravels the molecular diversity in mating loci maintained by long-term balancing selection

Abstract: Balancing selection, an evolutionary force that retains genetic diversity, has been detected in multiple genes and organisms, such as the sexual mating loci in fungi. However, to quantify the strength of balancing selection and define the mating-related genes require a large number of strains. In tetrapolar basidiomycete fungi, sexual type is determined by two unlinked loci, MATA and MATB. Genes in both loci define mating type identity, control successful mating and completion of the life cycle. These loci are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 109 publications
1
51
0
Order By: Relevance
“…The two species are broadly sympatric and can grow on the same host, and sometimes they are found together on the same substrate. They are in general phylogenetically well separated species (Kauserud and Schumacher 2003; Seierstad et al 2020; Peris et al 2022), but some individuals clustered incongruently for different loci in a previous study including only a few molecular markers (Seierstad et al 2020). Here, the authors suggested introgression or incomplete lineage sorting as possible explanations for the conflicting phylogenetic signals (Seierstad et al 2020).…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…The two species are broadly sympatric and can grow on the same host, and sometimes they are found together on the same substrate. They are in general phylogenetically well separated species (Kauserud and Schumacher 2003; Seierstad et al 2020; Peris et al 2022), but some individuals clustered incongruently for different loci in a previous study including only a few molecular markers (Seierstad et al 2020). Here, the authors suggested introgression or incomplete lineage sorting as possible explanations for the conflicting phylogenetic signals (Seierstad et al 2020).…”
Section: Introductionmentioning
confidence: 84%
“…Mycelia from fresh cultures, grown on 3% MEA with a nylon sheet between the MEA and the mycelia, were scraped off the plate and DNA was extracted using the E.Z.N.A. ® Fungal HP DNA Kit (Omega Bio-Tek, Norcross, GA, USA) according to the DNA extraction procedure explained in Peris et al (2022). Illumina libraries were prepared by the Norwegian Sequencing Center (NSC) as explained in Peris et al (2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations